Subsurface characterization at ground failure sites in adapazari, Turkey - Bray, J. D.; Sancio, R. B.; Durgunoğlu, T.; Youd, T. L.; Stewart, J. P.; Seed, R. B.; Çetin, O. K.; Baturay, M. B.; Christensen, C.; Karadayılar, T.; ÖNALP, AKIN (ASCE-AMER SOC CIVIL ENGINEERS, 1801 ALEXANDER BELL DR, RESTON, VA 20191-4400 USA, 2004)
Ground failure in Adapazari, Turkey during the 1999 Kocaeli earthquake was severe. Hundreds of structures settled, slid, tilted. and collapsed due in pail to liquefaction and ground softening. Ground failure was more severe adjacent to and under buildings. The soils that led to severe building damage were generally low plasticity silts. In this paper, the results of a comprehensive investigation of the soils of Adapazari, which included cone penetration test (CPT) profiles followed by borings with standard penetration tests (SPTs) and soil index tests, are presented. The effects Of Subsurface conditions on the Occurrence of ground failure and its resulting effect on building performance are explored through representative case histories. CPT- and SPT-based liquefaction triggering procedures adequately identified soils that liquefied if the clay-size criterion of the Chinese criteria was disregarded. The CPT was able to identify thin seams of loose liquefiable silt. and the SPT (with retrieved samples) allowed for reliable evaluation of the liquefaction Susceptibility of fine-grained soils. A well-documented database of in situ and index testing is now available for incorporating in future CPT- and SPT-based liquefaction triggering correlations.
Keywords: cone penetration tests; earthquakes; fine-grained soils; liquefaction; silts; in situ tests; subsurface environment; Turkey; liquefaction resistance; penetration test; koni penetrasyon testleri; depremler; ince taneli topraklar; sıvılaşma; silt; yerinde yapılan testlere; yeraltı ortamı; Türkiye; sıvılaşma direnci; penetrasyon testi